South Africa Economic Update, Edition 13 : Building Back Better from COVID-19 with a Special Focus on Jobs - World Bank (World Bank, Washington, DC, 2021)
South Africa is set to emerge from the crisis weaker than it had been going into it. However, this Economic Update argues that the reasons for low growth and high unemployment do not lie in the government’s crisis response, which has generally been sound. Growth is expected to reach 4 percent in 2021, slowing to 2.1 percent in 2022 and 1.5 by 2023. The global recovery is helping South Africa, especially given strong performance by China and the United States, two of its main trading partners. With deeper economic reforms, South Africa could benefit even more from the high growth in its trading partners. Low-wage workers suffered almost four times more job losses than did high-wage ones. Although a modest job recovery has started, it is at risk from the severe third wave of the pandemic. Self-employment represents only 10 percent of all jobs, as against 30 percent in most upper-middle-income economies, such as Turkey, Mexico, and Brazil. The emerging start-up sector in South Africa could help close this gap.